Haptic Interface For A Master Slave Robotic Gripper - Tay , Tee Tiong (2008)
A Master-slave haptic gripper system to recreate the feeling of relative hardness of different test objects is designed and built. Haptic is defined as dependent on feeling by touch rather than by sight. Haptic interfaces are devices which enable human to interact manually with virtual environments.